"Music, A Tool for Language Revitalization" - Ansah, M.A.; Adjei, G.; Agyeman, N.A. (My University, 2017)
This is a preliminary study which seeks to investigate ways in which music can be used to revitalize less-studied or minority languages. The study focuses on three South Guan languages in Ghana: Leteh, Kyerepong and Efutu. The relationship between language and music has been a subject of interest to a number of interdisciplinary scholars. Studies done in this area have observed that in notable respects, language and music are systematically comparable. For instance, the two are similarly constructed of functional and meaningful units; both possess phonemic and morphemic properties. Furthermore, the phonemic and morphemic units/properties are used to produce utterances by rules of sequencing and re-combination (Faudree 2013; Grant 2014; Kropp-Dakubu 2015; Lerdahl and Jackendoff 1983; Minks 2013). The observation that music and language have noteworthy parallels is therefore significant to this study. This study draws on the Affective Filter Hypothesis (Krashen 1982) which emphasizes the importance of positive emotions in language acquisition. Language surveys were conducted in Winneba, Larteh and Adukrom where the three languages are spoken. The study concludes that the theory behind the use of songs in teaching a second language can be extended to the teaching and learning of less-studied languages/minority languages and ultimately, their revitalization.
Seminar
Keywords: music; South Guan languages; Ghana; phonemic; morphemic